PENGUASAAN GURU MATEMATIKA SEKOLAH MENENGAH TERHADAP PEMBELAJARAN INOVATIF BERBASIS PENELITIAN MELALUI KEGIATAN LESSON STUDY - Rohaeti, Euis Eti; Hendriana, Heris (Universitas Pendidikan Indonesia, 2016)
This is a descriptive study aimed to examine mathematics teachers’ ability to master various research-based innovative teaching approaches and their ability to plan, implementi, and assess their teaching and learning procesess. The subjects of this study are 16 mathematics teachers from four different districts in West Java who collaborated with 8 post-gradute students of STKIP Siliwangi Bandung as a part of Lesson Study program. The instruments of this study are an observation sheet and writen and oral interview with the teachers. The study revealed that:1) The teachers’ ability on mastering various innovative teaching learning approaches based on a research was at low level; 2) Teachers’ ability on planning, implementing, and assessing their teaching and learning process was at medium level; 3) There is high association between teachers’ ability on mastering various innovative teaching learning approaches based on a research and their abilities on planning and implementing teaching-learning process; 4) There is medium associationbetween teachers’ ability on mastering various innovative teaching learning approaches based on a research and their ability on assessing their teaching-learning process; 5) Lesson Study Activities between teachers and students as an effort to share reseacrh outcomes of university lecturers with school teachers. ABSTRAKPenelitian ini merupakan penelitian deskriptif yang bertujuan menelaah penguasaan guru matematika terhadap beragam pembelajaran inovatif berbasis penelitian yang dikaitkan dengan kemampuan guru dalam merencanakan, melaksanakan dan mengevaluasi pembelajaran yang dilakukannya. Subjek penelitian terdiri dari 16 orang guru sekolah menengah yang berasal dari 4 kabupaten yang berbeda di Jawa Barat yang berkolaborasi dengan 8 mahasiswa pasca sarjana Pendidikan Matematika dari sebuah STKIP di Badung dalam rangka kegiatan Lesson Study. Pengambilan data dilakukan melalui observasi pembelajaran dan wawancara lisan dan tertulis dengan guru tersebut. Hasil penelitian menunjukkan bahwa: 1) Penguasaan guru matematika terhadap beragam pembelajaran inovatif berbasis penelitian masih berada pada level rendah; 2) Kemampuan merencanakan, melaksanakan, dan mengevaluasi pembelajaran berada pada level sedang; 3) Terdapat asosiasi yang tinggi antara penguasaan guru matematika terhadap beragam pembelajaran inovatif berbasis penelitian dengan kemampuan merencanakan dan melaksanakan pembelajaran; 4) Terdapat asosiasi yang sedang antara penguasaan guru matematika terhadap beberapa pembelajaran inovatif berbasis penelitian dengankemampuan mengevaluasi pembelajaran; 5) KegiatanLesson Study antara guru dan mahasiswa merupakan upaya mendiseminasikan hasil penelitian para akademisi kepada guru di sekolah.